Innovative Hurdle Technologies for the Preservation of Functional Fruit Juices - Predrag Putnik; Branimir Pavlić; Branislav Šojić; Sandra Zavadlav; Irena Žuntar; Leona Kao; Dora Kitonić; Danijela Bursać Kovačević (Foods, 2020)
Functional nutrition, which includes the consumption of fruit juices, has become the field of interest for those seeking a healthy lifestyle. Functional nutrition is also of great interest to the food industry, with the aims of improving human health and providing economic prosperity in a sustainable manner. The functional food sector is the most profitable part of the food industry, with a fast-growing market resulting from new sociodemographic trends (e.g., longer life expectancy, higher standard of living, better health care), which often includes sustainable concepts of food production. Therefore, the demand for hurdle technology in the food industry is growing, along with the consumption of minimally processed foods, not only because this approach inactivates microorganisms in food, but because it can also prolong the shelf life of food products. To preserve food products such as fruit juices, the hurdle technology approach often uses non-thermal methods as alternatives to pasteurization, which can cause a decrease in the nutritional value and quality of the food. Non-thermal technologies are often combined with different hurdles, such as antimicrobial additives, thermal treatment, and ultraviolet or pulsed light, to achieve synergistic effects and overall quality improvements in (functional) juices. Hence, hurdle technology could be a promising approach for the preservation of fruit juices due to its efficiency and low impact on juice quality and characteristics, although all processing parameters still require optimization.